Embodying an outgroup: the role of racial bias and the effect of multisensory processing in somatosensory remapping - Fini, Chiara; Cardini, Flavia; Tajadura-Jimenez, Ana; Serino, Andrea; Tsakiris, Manos (Frontiers in Behavioral Neuroscience, 2013)
We come to understand other people’s physical and mental states by re-mapping their bodily states onto our sensorimotor system. This process, also called somatosensory resonance, is an essential ability for social cognition and is stronger when observing ingroup than outgroup members. Here we investigated, first, whether implicit racial bias constrains somatosensory resonance, and second, whether increasing the ingroup/outgroup perceived physical similarity results in an increase in the somatosensory resonance for outgroup members. We used the Visual Remapping of Touch effect as an index of individuals’ ability in resonating with the others, and the Implicit Association Test to measure racial bias. In Experiment 1, participants were asked to detect near-threshold tactile stimuli delivered to their own face while viewing either an ingroup or an outgroup face receiving a similar stimulation. Our results showed that individuals’ tactile accuracy when viewing an outgroup face being touched was negatively correlated to their implicit racial bias. In Experiment 2, participants received the Interpersonal Multisensory Stimulation (IMS) while observing an outgroup member. IMS has been found to increase the perceived physical similarity between the observer’s and the observed body. We tested whether such increase in ingroup/outgroup perceived physical similarity increased the remapping ability for outgroup members. We found that after sharing IMS experience with an outgroup member, tactile accuracy when viewing touch on outgroup faces increased. Interestingly, participants with stronger implicit bias against the outgroup showed larger positive change in the remapping. We conclude that shared multisensory experiences might represent one key way to improve our ability to resonate with others by overcoming the boundaries between ingroup and outgroup categories.